The Effect of K2CO3 and Ca(OH)2 Catalysts on The Yield of Syngas Products and Tar Production on Tobacco Waste Gasification with Downdraft Gasifier Type - Suhendi, Endang; Dahlin, Julianus Marthin; Almundzir, Yahya (World Chemical Engineering Journal, 2017)
Nowadays tobacco waste from cigarette production has not been managed properly, only used as fuel on direct combustion process that caused air pollution. To resolve it, indirect combustion method or gasification can be used. Gasification is a thermochemical process that converts solid fuel into a gas capable of fuel known as Synthesis Gas by a combustion process using limited oxygen. Fuel gases and synthesis gases produced by the gasification is used as power generation, heating, chemical products, etc. However, gasification processes also generated condensable organic compounds, so called “tar”. As the processing method, using the catalytic tar decomposition has been widely studied. The purposes of this study is to determine the effect of catalysts K2CO3 and Ca(OH)2 on increasing the composition of synthesis gas produced and decreasing the amount of tar produced. As for the steps of this research are preparation of raw materials, gasification process and analyzing the composition of the syngas. The experimental results show that alkali metal compound (K2CO3) and alkaline earth metal compound (Ca(OH)2) have a catalytic effect to decompose tar contents, to enhance gaseous production. The largest syngas composition produced by the use of Ca(OH)2 catalyst with H2= 10,20 %v; CO = 21,81 %v; dan CH4 = 2,02 %v. On tar reduction, Ca(OH)2 catalyst was better than K2CO3 catalyst with tar production reduced by 34,04%v.